Perkembangan Teknologi Komunikasi dan Informasi: Akar Revolusi dan Berbagai Standarnya - Yusniah Yusniah; Audina Putri; Anggraini Simatupang (Da'watuna: Journal of Communication and Islamic Broadcasting, 2023)
Information is the main element that is implicit in the concept of planned development. Although the role of information has been underappreciated for decades, in fact the need for communication and information is something that is no less important than the need for human food and clothing. Implementation activities can only run and achieve targets at each stage of monitoring and planning on the basis of adequate information. Furthermore, information can be obtained from a communication but it is actually the one that affects the value of the communication that is the information carried. For the information revolution, it is generally understood as a change that is derived from IT (information technology). There are two types of communication technology for humans, namely the technology used to disseminate information and the computer system used to process it. Let's say revolution because it can have such a rapid impact on the human environment. Then the basic factors contained in communication and information technology are standards. The development of the network really requires a standard operating system. If someone uses a network to be able to communicate with someone, actually indirectly requires a system that is compatible with one another. the relationship between networks, standards and systems such as glue to develop communication between people. As for technology, it can have some positive or negative effects, but it is related to the problems and dynamics of increasing advanced technology, therefore each individual and society in a country can be the master of technology and vice versa become a society that is controlled and controlled by technology. Keywords: Technology, Information and communication revolution, Technology standar